O empoderamento da mulher: um estudo empírico da Feira do Produtor de Toledo/Pr - Andrade, Fabiola Juliana Rubim de (2010)
The dissertation was to understand how central concern is women's life strategies, leading to their empowerment. To understand this process, in other words, the empowerment of women, was conducted case study of women producers rural and urban residents of Toledo County who market their products at the Fair of the Producer of the Municipality. It is considered in this study the Fair Producer of Toledo as a social place, where not are only marketed products hand made or from family farming production (such as vegetables, breads, pastries, snacks, sausages, etc.). But, also as a place that offers the potential for accelerating the processes of social change, as manifested in the case studied, through the confluence of several social people, which interact with the aim of changing socioeconomic conditions of their families and their own condition. It is believed, and this is the hypothesis of this dissertation, this will occurs with women participants, who occupy the space at the fair to empower different ways. Was adopted a qualitative methodology, collecting empirical data through of collective and individual interviews, participant observation, rescue of fragments of memories and experiences. The survey found that although most of the workers interviewed the family budget to be covered by income women it is still being controlled by man. Highly prevalent in men to determine what the family should get to eat food, for clothing and other necessities. However, there is a break in the male control because, in that the awareness of women regarding various aspects of their daily life, turns to the work at the Fair of the Producer, the consensus that sustains male power weakens. The process of empowerment of women surveyed still is subtle, because they are influenced by a paternalistic society, and consider her work as a simple aid to her comrades and families. Moreover, these same women feel valued, as they break in one way or another, with the culture that power belongs to the man, puraly because it leaves the family context and get "help" of his comrades and families in work previously considered exclusively female, such as housework and caring with children.